Case Report: Giant Cell Tumor of Tendon Sheath After Breast Augmentation - Zhang, Yu; Fan, Yingying; Zhang, Hongying; Bu, Hong; Chen, Min; Yang, Jieliang; Zhang, Zhang (Frontiers in Oncology, 2022)
Giant cell tumor of tendon sheath (GCTTS) is a benign tumor. It occurs predominantly in the hands, ankles, and knees. A 39-year-old female presented with GCTTS in the right breast after breast augmentation. There was a clear borderline between the tumor and breast tissue. In morphology appearance, synovial metaplasia could be observed in part of the collagenous capsule. The tumor was moderately cellular and was composed of synovium-like monocytes. The main part of tumor was blended with nested and scattered xanthomatous cells, lymphocytes, and osteoclast-like giant cells. Hemosiderin granules were distributed in the lesion. The immunohistochemical staining and fluorescence in situ hybridization analyses were performed. CD68 staining was positive in osteoclast-like giant cells. In addition, neither significant USP6 translocation nor CSF1 translocation was detected by FISH. We hypothesized the pathogenesis of this rare GCT-TS was based on synovial metaplasia and didn’t depend on the translocation of classical CSF1.